Parenting and Turkish children's behaviour problems: the moderating role of qualities of parent-child relationship - Acar, Ibrahim H.; Ucus, Sukran; Yildiz, Suleyman (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
The current study is an examination of contributions of parenting styles and qualities of parent-child relationship (PCR) to Turkish children's externalizing and internalizing behaviours, with a specific focus on the moderating role of PCR (closeness and conflict) on parenting styles (authoritarian and democratic/authoritative) when predicting children's externalizing and internalizing behaviours. Participants were 94 children (56 boys) with the mean age of 7.05 years (SD = 0.88) in a suburban district in Turkey. Mothers reported on their parenting styles and relationships with their children as well as children's externalizing and internalizing behaviours. Results from regression analyses showed that parent-child closeness significantly moderated the association between authoritarian parenting and children's externalizing behaviours. Parent-child conflict significantly moderated the association between authoritarian parenting and children's internalizing behaviours. The parent-child conflict was positively associated with children's externalizing behaviour and authoritarian parenting was positively associated with internalizing behaviour. Limitations and future directions of the current study are discussed.
Keywords: Turkish children; externalizing behaviour; internalizing behaviour; parent-child relationship; parenting styles; CONDUCT PROBLEMS; EMOTIONAL INTELLIGENCE; EXTERNALIZING BEHAVIOR; NEGATIVE EMOTIONS; SOCIAL COMPETENCE; FAMILIES; STYLES; RISK; SOCIALIZATION; CONTEXT; Education & Educational Research; Psychology